Safety First! Residential Group Climate and Antisocial Behavior: A Multilevel Meta-analysis - E. M. A, Eltink (International journal of offender therapy and comparative criminology, 2025)
A systematic review and multilevel meta-analysis was performed (28 studies and 313 effect sizes) on the relation between residential group climate (i.e., safety, atmosphere, repression, support, growth, structure) and antisocial behavior, including aggression and criminal recidivism. A systematic search was conducted in PsychINFO, ERIC, and OVID Medline up to February 2023. Results showed a small but significant association (r = .20) between residential group climate and antisocial behavior, equivalent to a 23% reduction of antisocial behavior in all clients receiving care in a residential facility with a therapeutic group climate. Moderator analyses showed that experienced safety was more strongly related to antisocial behavior (r = .30) than the other dimensions of group climate (.17 < r < .20), while the effect size was somewhat larger for adults (r = .24) than for youth (r = .15). We conclude that residential facilities should consider safety as a priority and should involve clients in a positive process of change through the development of a therapeutic environment and delivery of evidence-based treatment, addressing their needs from the perspective of rehabilitation.